Set up of cutoff thresholds for kinship determination using SNP loci. (July 2017) - Cho, Sohee; Shin, Eun Soon; Yu, Hyung Jin; Lee, Ji Hyun; Seo, Hee Jin; Kim, Moon Young; Lee, Soong Deok
Highlights: Discriminatory power of 80 SNP loci was suitable for parent-child relationships. Applying 136 SNP loci applied to analysis was sufficient for full-sibling determination with the highest accuracy and sensitivity. Indistinguishable full-sibling relationships with only 15 STR data were successfully resolved by SNP data with significant difference in the median value. Abstract: The usefulness of single nucleotide polymorphism (SNP) loci for kinship testing has been demonstrated in many case works, and suggested as a promising marker for relationship identification. For interpreting results based on the calculation of the likelihood ratio (LR) in kinship testing, it is important to prepare cutoffs for respective relatives which are dependent on genetic relatedness. For this, analysis using true pedigree data is significant and reliable as it reflects the actual frequencies of markers in the population. In this study, the kinship index was explored through 1209 parent-child pairs, 1373 full sibling pairs, and 247 uncle-nephew pairs using 136 SNP loci. The cutoffs for LR were set up using different numbers of SNP loci with accuracy, sensitivity, and specificity. It is expected that this study can support the application of SNP loci-based kinship testing for various relationships.